A simple, rapid and economic manual method for human sperm DNA extraction in genetic and epigenetic studies - Mahsa Darbandi; Sara Darbandi; Hamid Reza Khorram Khorshid; Mohammad Mehdi Akhondi; Pooneh Mokarram; Mohammad Reza Sadeghi (Middle East Fertility Society Journal, 2018)
Over the recent years, isolation of high quantities of pure, intact, double-stranded, highly concentrated and not contaminated genomic DNA is prerequisite for successful and reliable large scale genetic and epigenetic analysis and also high quantities of pure DNA are required for these types of studies. The DNA extraction methods developed for human somatic cells are not effective for sperm because of the high rating of nuclear compaction and DNA integrity in sperm cells. In the present study, an economic, reliable and simple method of DNA extraction procedures, were examined to ascertain their relative effectiveness for extracting DNA from human sperm. The quality and quantity of the extracted DNA were assessed by spectrophotometric measurements, methylation-specific PCR (MSP) amplification, and gel electrophoresis. This method was applied successfully from sperm samples (N = 50, age = 33.9 ± 7.8 years) with DNAs absorbency ratios of A260/A280 (1.82 ± 0.03) and A260/230 (1.95 ± 0.16). Gel electrophoresis revealed non-degraded and suitable quality genomic DNA for epigenetic and genetic analysis. The purity and quality of this protocol was closer to the optimum value sand no contamination during manual extraction was observed. It concluded that this described method might have a sufficient quality for subsequent molecular analysis and general genetic and epigenetic methods. Keywords: Absorbency ratios, DNA concentration, Genetic and epigenetic studies, Protamine, Proteinase K, Sperm DNA extraction, TRIzol